A TRACER culture invasion assay to probe the impact of cancer associated fibroblasts on head and neck squamous cell carcinoma cell invasiveness. (29th April 2020) - Dean, Teresa; Li, Nancy T.; Cadavid, Jose L.; Ailles, Laurie; McGuigan, Alison P.
Abstract : A novel 3D in vitro co-culture platform to explore the interactions between cancer-associated fibroblasts and tumour cells that drive increased tumour cell invasion and the impact of matrix density. Abstract : Cancer associated fibroblasts (CAFs) are a major cellular component of the tumour stroma and have been shown to promote tumour cell invasion and disease progression. CAF–cancer cell interactions are bi-directional and occur via both soluble factor dependent and extracellular matrix (ECM) remodelling mechanisms, which are incompletely understood. Previously we developed the Tissue Roll for Analysis of Cellular Environment and Response (TRACER), a novel stacked paper tumour model in which cells embedded in a hydrogel are infiltrated into a porous cellulose scaffold that is then rolled around an aluminum core to generate a multi-layered 3D tissue. Here, we use the TRACER platform to explore the impact of CAFs derived from three different patients on the invasion of two head and neck squamous cell carcinoma (HNSCC) cell lines (CAL33 and FaDu). We find that co-culture with CAFs enhances HNSCC tumour cell invasion into an acellular collagen layer in TRACER and this enhanced migration occurs independently of proliferation. We show that CAF-enhanced invasion of CAL33 cells is driven by a soluble factor independent mechanism, likely involving CAF mediated ECM remodelling via matrix metalloprotenases (MMPs). Furthermore, we find that CAF-enhanced tumour cell invasion is dependent on the spatial pattern of collagen density within the culture. Our results highlight the utility of the co-culture TRACER platform to explore soluble factor independent interactions between CAFs and tumour cells that drive increased tumour cell invasion.